Histologia e histoquímica do intestino anterior de tilápia do Nilo (Oreochromis niloticus) alimentadas com dietas contendo silagem de peixe - Honorato, Claucia Aparecida; da Cruz, Claudinei [UNESP]; Carneiro, Dalton José [UNESP]; Márcia, Rita Fernandes Machado [UNESP] (My University, 2011)
This work was carried out to evaluate the action of the fermented fish silage and fish meal in the histochemical of the middle intestine of O. niloticus. A great epithelium intestinal was present in fishes fed with fish silage, independent of the animal origin protein proportions in diets. It was observed that the variation of the goblet cells secretion glicoproteic intensity is linked directly to the diet supplied to animals. The middle intestine of Oreochromis niloticus showed differences in the neutral mucus glicoproteic, acid glicoproteic and glicoconjugated secretion pattern, depending on the protein origin and the percentage used in the diet, demonstrating that this species can adapt its secretion system for the protection of the digesting apparatus during the absorption of different protein sources.
Histology and histochemical the medium intestine in Nile tilapia (Oreochromis niloticus) fed diets with fish silage
Keywords: Fish silage; Histology of intestine; Oreochromis niloticus; Animalia; Pisces